2022
DOI: 10.1016/j.heliyon.2022.e08914
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of dermal exposure to heavy metals (Cu, Zn, Ni, Al, Fe and Pb) in traditional batik industry workers

Abstract: Batik is an Indonesian cultural heritage that has been designated by UNESCO. Batik industry is one of the industries that applies the synthetic dyes, beside natural ones which have long been used in producing Batik particularly in the modern production. The purpose of this research investigated heavy metals on workers in batik industry, which focuses on dermal detection as portal of entry. Samples of dermal intake of workers were examined with cross-sectional approach, while non-worker samples of resident livi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Additionally, chrome or mordant dyes and metal complex dyes are utilized to achieve bright and dark colors. Most dyes contain heavy metals, including lead (Pb), arsenic (As), chromium (Cr), nickel (Ni), copper (Cu), cadmium (Cd), mercury (Hg), and zinc (Zn) ( Table 2 ) [ 55 , 56 , 57 ]. Generally, heavy metals with a density of greater than 5 mg/cm 3 are considered to have a high density.…”
Section: Textile Functionalization As the Source Of Microfiber Toxicitymentioning
confidence: 99%
“…Additionally, chrome or mordant dyes and metal complex dyes are utilized to achieve bright and dark colors. Most dyes contain heavy metals, including lead (Pb), arsenic (As), chromium (Cr), nickel (Ni), copper (Cu), cadmium (Cd), mercury (Hg), and zinc (Zn) ( Table 2 ) [ 55 , 56 , 57 ]. Generally, heavy metals with a density of greater than 5 mg/cm 3 are considered to have a high density.…”
Section: Textile Functionalization As the Source Of Microfiber Toxicitymentioning
confidence: 99%
“…Synthetic colorants used in the batik coloring process contain some heavy metals. In previous study, we found that the dominant synthetic dyes used in the batik production in the study area were remazol, naphthol, and indigosol, and the heavy metals detected were Cu, Zn, Ni, Al, Fe, and Pb [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have explored the presence of heavy metals in the batik industry, focusing on wastewater [ 2 , 3 ], dyestuffs [ 1 ], and impact on water bodies and biota [ 4 , 5 ]. Previously, a research have confirmed the dermal exposure of lead among batik industry workers [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The textile can be made of natural or synthetic fibers and the whole production process involves extensive use of chemicals. The main chemical pollutants present in textiles are dyes containing carcinogenic amines, metals, pentachlorophenol, chlorine bleaching, halogen carriers, free formaldehyde, biocides, fire retardants, and softeners [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%